Implementation of the Suggestopedia Method to Improve Student Learning Motivation in Islamic Cultural History Subjects at MTs. N 3 Gorontalo Regency - Faizal Fatah SN Tuli (Al-Ulum: Jurnal Pendidikan Islam, 2026)
The low learning motivation of students in the subject of Islamic Cultural History (ISCH) remains a significant issue in the madrasah environment, especially when learning is monotonous, lecture-centered, and does not provide a comfortable learning atmosphere. In this context, the suggestopedia method is considered relevant because it emphasizes relaxation, positive suggestions, a pleasant classroom atmosphere, and supportive pedagogical interactions. This study aims to explain in depth the implementation of the suggestopedia method in ISCH learning at MTs. N 3 Gorontalo Regency and reveal its contribution to increasing student learning motivation. This study uses a qualitative approach with a case study design. The results show that the implementation of suggestopedia contributes to increasing student learning motivation in ISCH subjects. The implications of this study emphasize that increasing learning motivation in ISCH learning is not only determined by the variety of methods, but also by the teacher's ability to build a safe, calm, and meaningful learning atmosphere. Therefore, suggestopedia can be considered as a relevant pedagogical alternative in strengthening the quality of learning in madrasahs.